Population Pharmacokinetics of Intravenous Artesunate: A Pooled Analysis of Individual Data From Patients With Severe Malaria. (5th November 2014) - Zaloumis, S G; Tarning, J; Krishna, S; Price, R N; White, N J; Davis, T M E; McCaw, J M; Olliaro, P; Maude, R J; Kremsner, P; Dondorp, A; Gomes, M; et al.
Abstract : There are ~660, 000 deaths from severe malaria each year. Intravenous artesunate (i.v. ARS) is the first‐line treatment in adults and children. To optimize the dosing regimen of i.v. ARS, the largest pooled population pharmacokinetic study to date of the active metabolite dihydroartemisinin (DHA) was performed. The pooled dataset consisted of 71 adults and 195 children with severe malaria, with a mixture of sparse and rich sampling within the first 12 h after drug administration. A one‐compartment model described the population pharmacokinetics of DHA adequately. Body weight had the greatest impact on DHA pharmacokinetics, resulting in lower DHA exposure for smaller children (6–10 kg) than adults. Post hoc estimates of DHA exposure were not significantly associated with parasitological outcomes. Comparable DHA exposure in smaller children and adults after i.v. ARS was achieved under a dose modification for intramuscular ARS proposed in a separate analysis of children. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e145; doi:10.1038/psp.2014.43 ; published online 05 November 2014